Prevalence and characterization of findings associated with implants in panoramic radiographs - Silvia Barrientos Sánchez; Adriana Rodríguez Ciodaro; David Martínez Laverde; Alejandro Curan Cantoral (Editorial Ciencias Médicas, 2018)
Introduction: the most recent survey about oral health conducted in Colombia revealed that nearly 70 % of the population is partially edentulous, whereas 5.2 % will have lost all their teeth by the time they are 65-79 years old. Implant rehabilitation is an ever more common alternative which requires clinical and radiographic follow-up, panoramic radiography being a low-cost option to observe areas of bone loss, mesiodistal angulation of the implant, relationship to anatomical structures and lesions suggesting peri-implantitis. Relevant data analyses and reports are needed about radiographic findings associated with dental implants to determine the risk factors for their success in patients wearing them. Objective: determine the prevalence of and characterize the findings associated to osseointegration implants in panoramic radiographs. Methods: a cross-sectional observational descriptive study was conducted of 10 000 digital panoramic radiographs chosen by convenience sampling at radiology centers from the city of Bogotá, Colombia, of which 543 made up the study sample, due to the presence of implants. Each implant was evaluated for location, position, angulation and distance from adjacent structures, using the software Clínicalview® (Orthopantomograph OP200D, Instrumentarium, USA). Results: the frequency of radiographs with implants was 5.43 % with a total 1 791 implants and an average 3.2 per radiograph. Implants were more common on the upper maxilla with a supracrestal location and an angulation of 10.3 degrees. In 32 % implant-tooth or implant-implant distances were below optimum values. 40.9 % had been restored and 1.2 % showed lesions compatible with peri-implantitis. Conclusions: a large proportion of the implants examined exhibit a risk factor affecting their long-term viability, namely angulation, supracrestal or crestal position, proximity to teeth or other implants, or not being restorable.